Fluorine labelling of therapeutic human tolerogenic dendritic cells for 19F-magnetic resonance imaging - Cooke, Fiona; Neal, Mary; Wood, Matthew J.; de Vries, I. Jolanda M.; Anderson, Amy E.; Diboll, Julie; Pratt, Arthur G.; Stanway, James; Nicorescu, Ioana; Moyse, Nicholas; Hiles, Dawn; Caulfield, David; et al. (Frontiers in Immunology, 2022)
Tolerogenic dendritic cell (tolDC) therapies aim to restore self-tolerance in patients suffering from autoimmune diseases. Phase 1 clinical trials with tolDC have shown the feasibility and safety of this approach, but have also highlighted a lack of understanding of their distribution in vivo. Fluorine-19 magnetic resonance imaging (19F-MRI) promises an attractive cell tracking method because it allows for detection of 19F-labelled cells in a non-invasive and longitudinal manner. Here, we tested the suitability of nanoparticles containing 19F (19F-NP) for labelling of therapeutic human tolDC for detection by 19F-MRI. We found that tolDC readily endocytosed 19F-NP with acceptable effects on cell viability and yield. The MRI signal-to-noise ratios obtained are more than sufficient for detection of the administered tolDC dose (10 million cells) at the injection site in vivo, depending on the tissue depth and the rate of cell dispersal. Importantly, 19F-NP labelling did not revert tolDC into immunogenic DC, as confirmed by their low expression of typical mature DC surface markers (CD83, CD86), low secretion of pro-inflammatory IL-12p70, and low capacity to induce IFN-gamma in allogeneic CD4+ T cells. In addition, the capacity of tolDC to secrete anti-inflammatory IL-10 was not diminished by 19F-NP labelling. We conclude that 19F-NP is a suitable imaging agent for tolDC. With currently available technologies, this imaging approach does not yet approach the sensitivity required to detect small numbers of migrating cells, but could have important utility for determining the accuracy of injecting tolDC into the desired target tissue and their efflux rate.